2016
DOI: 10.3389/fmicb.2016.01222
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Evolution of Sporulation in Bacillus thuringiensis Biofilm

Abstract: Bacillus thuringiensis can produce a floating biofilm which includes two parts: a ring and a pellicle. The ring is a thick structure which sticks to the culture container, while the pellicle extends over the whole liquid surface and joins the ring. We have followed over time, from 16 to 96 h, sporulation in the two biofilm parts. Sporulation was followed in situ in 48-wells polystyrene microtiterplates with a fluorescence binocular stereomicroscope and a spoIID-yfp transcriptional fusion. Sporulation took plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Importantly, the ability of these bacteria to produce the biofilms in the glass test tubes with SOBG broth was not examined yet. Definitely, certain strains of E. coli ( Weiss-Muszkat et al, 2010 ; Hung et al, 2013 ), P. fluorescens ( Spiers et al, 2003 ; Koza et al, 2009 ), K. pneumoniae ( Wang et al, 2016 ), A. lwoffii ( Martí et al, 2011 ), and B. thuringiensis ( El-Khoury et al, 2016 ) from other than wastewater origins have been reported to form the AL biofilms in defined laboratory systems. In this study, E. asburiae ENSD102 (from dyeing wastewater), uncultured Vitreoscilla sp.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the ability of these bacteria to produce the biofilms in the glass test tubes with SOBG broth was not examined yet. Definitely, certain strains of E. coli ( Weiss-Muszkat et al, 2010 ; Hung et al, 2013 ), P. fluorescens ( Spiers et al, 2003 ; Koza et al, 2009 ), K. pneumoniae ( Wang et al, 2016 ), A. lwoffii ( Martí et al, 2011 ), and B. thuringiensis ( El-Khoury et al, 2016 ) from other than wastewater origins have been reported to form the AL biofilms in defined laboratory systems. In this study, E. asburiae ENSD102 (from dyeing wastewater), uncultured Vitreoscilla sp.…”
Section: Discussionmentioning
confidence: 99%
“…5f). In addition, 5 induced macroscopically visible aggregation and classical biofilm ring formation of Δmuf mutant 49 . Furthermore, the addition of 5 to the wild-type or the Δmuf mutants of Smu56 and Smu57 significantly decreased the polar electron-donor (γ -) parameter of bacterial surface ( Fig.…”
Section: Direct Effect Of Mutanofactin On Biofilm Formation the Genementioning
confidence: 98%
“…Additionally, in certain conditions this may also result in higher total numbers of spores eventually formed in the biofilms compared to the surrounding planktonic phase, as observed in Chapter 2. The onset of sporulation in the ring of an air-liquid interface biofilm of B. thuringiensis was also shown to precede the sporulation in the pellicle type biofilm in the same setting, presumably linked to the earlier nutrient limitation experienced in the ring compared to the pellicle (El-Khoury et al 2016). …”
Section: Sporulation Within Biofilms and Spore Propertiesmentioning
confidence: 90%
“…2. Recently, El-Khoury et al (El-Khoury et al 2016) analysed sporulation efficacy in B. thuringiensis air liquid interface biofilms and presented a model describing spore formation in the biofilm, the impact of mechanical washing and cleaning causing only partial removal of biofilm spores, and the role of residual spores in starting a new biofilm after germination and outgrowth. Since the environment is known to affect the onset and efficiency of sporulation (Driks 2002, Piggot and Hilbert 2004, Abbas et al 2014, the conditions that biofilm cells encounter in the production environment, such as fluctuations in nutrient availability or air exposure, may affect the amount of spores formed, which in turn will affect the risk related to those biofilms.…”
Section: Influence Of Environmental Factors: Iron Sources and Biofilmmentioning
confidence: 99%
See 1 more Smart Citation